2015
DOI: 10.1055/s-0041-107897
|View full text |Cite
|
Sign up to set email alerts
|

Adenomas involving the extrahepatic biliary tree are rare but have an aggressive clinical course

Abstract: Biliary adenomas that are usually found in surgically removed gallbladders are rare, but can also occur in the extrahepatic biliary tree. We present a case series of extrahepatic bile duct adenomas at our institution, along with a review of the literature. All three patients with extrahepatic biliary adenomas (two in the common bile ducts, one in the hepatic duct) were female with a mean age of 74 years. On initial presentation, none of the patients had obstructive jaundice but two of the three patients had sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Cholangioadenoma is described relatively infrequently within literature and rarely seen in clinical practice 1 2 3 4 5 6 7 8 9 . There have been collectively fewer than 50 cases of cholangioadenoma described in literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cholangioadenoma is described relatively infrequently within literature and rarely seen in clinical practice 1 2 3 4 5 6 7 8 9 . There have been collectively fewer than 50 cases of cholangioadenoma described in literature.…”
Section: Discussionmentioning
confidence: 99%
“…They also recognize the difficulty in diagnosis using standard imaging techniques given potential to misdiagnose as CBD stones, sludge or even cholangiocarcinoma, helped in their case by using contrast enhancement 3 . Loh et al provide the most extensive and recent literature review on bile duct adenomas as part of their case series published in 2015 9 . In all three cases in their series, the patients went on to develop malignancy on follow-up of their bile duct adenoma, and they propose the potential for an “aggressive” course with these seemingly benign tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenomas of the extrahepatic bile duct are uncommon benign neoplasms with an unknown malignant potential [1 -3]. Surgery is the current treatment [1 -3], with only five published cases of successful endoscopic treatment in nonsurgical patients [2]. In the current case, the key to achieving technical success was good visualization through the papilla (papilloplasty + stent) and the use of a pediatric polypectomy snare with the help of the balloon.…”
mentioning
confidence: 95%
“…However, they can occur anywhere in the extra-hepatic bile ducts with uncertain malignant potential, and there are still no guidelines for their management. A review conducted by Loh et al ( 2 ) found that a total of 39 cases of bile tree adenomas have been reported till date. Different imaging modalities have been used for identifying these tumors with varying success rates, including contrast-enhanced ultrasound, intraductal ultrasound, and even 18 F-fluorodeoxyglucose uptake ( 3 , 4 ).…”
mentioning
confidence: 99%